Pengaruh Service Quality, Learning Quality, dan Word of Mouth Terhadap Keputusan Wali Murid Memilih SD Negeri Tunggak Kecamatan Bojonegara - Buya Aina Ambiya; Muhamad Suhaemi; Abdul Fatah (Universitas Serang Raya, 2023)
This study aims to determine whether service quality, learning quality, and word of mouth influence parents' decisions to choose Tunggak Elementary School in Bojonegara Sub-District. This research was conducted using a quantitative method. The sampling method used was probability sampling with a simple random sampling technique. The sample in this study consisted of 72 parents of students at Tunggak Elementary School. The results of the research indicate that 1) service quality significantly influences parents' decisions to choose Tunggak Elementary School, 2) learning quality significantly influences parents' decisions to choose Tunggak Elementary School, 3) word of mouth significantly influences parents' decisions to choose Tunggak Elementary School, 4) service quality, learning quality, and word of mouth together significantly influence parents' decisions to choose Tunggak Elementary School. Based on the research results, it can be concluded that service quality, learning quality, and word of mouth have a parcial and simultaneous influence on parents' decisions to choose Tunggak Elementary School. Keywords: Service Quality, Learning Quality, Word of Mouth, Purchase Decision